"They are among the Best Workers, Learning the Ways of a Vineyard Quickly": Aboriginal People, Drinking, and Labor in the Early Australian Wine Industry. Issue 1 (4th May 2019) - McIntyre, Julie; Brady, Maggie; Barnes, Jillian
ABSTRACT: Studies of the impact of European forms of alcohol on Indigenous peoples tend to focus on health and social problems arising from overconsumption. This article takes a new approach by, first, parsing wine from the non-culturally specific treatment of all forms of alcohol in the lives of Aboriginal Australians; and, second, considering Aboriginal employment in Australian wine production since the early nineteenth century alongside these peoples' exclusion from the late-twentieth century rise of an Australian "good life" of democratized wine drinking practices. By re-entangling these elements of Aboriginal lives in settler colonial society, we reveal an unknown facet of Aboriginal economic contribution, highlight relationships between Aboriginal- and Italian-Australians, and challenge negative stereotypes that Aboriginal Australians are unable to control themselves in the presence of alcohol.